2020
DOI: 10.3390/medsci8030026
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Contrast-to-Noise Ratio on Measurements to Evaluate CT Image Quality in Terms of Low-Contrast Detailed Detectability

Abstract: Background: To evaluate contrast-to-noise ratio (CNR) measurements in assessing image quality, in the context of the detectability performance of low-contrast detail (LCD), in computed tomography (CT) images, since exposure to elevated ionising-type radiation is considered to present excessive carcinogenic risk, whilst also causing distress in study subjects. Methods: An LCD phantom module (CTP515) was utilised in the study. Three dissimilar contrast items were used to analyse the ramifications of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…It was found that if noise level increases, then the target size also increases, as reported previously. 30,31 This is because the high levels of noise affect the shape of the sharp edge of the object, reducing the MDC especially for small objects.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that if noise level increases, then the target size also increases, as reported previously. 30,31 This is because the high levels of noise affect the shape of the sharp edge of the object, reducing the MDC especially for small objects.…”
Section: Discussionmentioning
confidence: 99%
“…Further details regarding the region of interest (ROI) selection and CNR computation are elaborated in the subsequent CT number accuracy section. Since the standard deviation of the CT number is inversely proportional to the square root of the tube current (mAs), 19 tube current‐normalized CNR was calculated by dividing the CNR and noise with the square root of the tube current (CNR/mAs$CNR/\sqrt {mAs} $) to exclude the impact of the different tube currents of each protocol 18–20 …”
Section: Methodsmentioning
confidence: 99%
“…Since the standard deviation of the CT number is inversely proportional to the square root of the tube current (mAs), 19 tube current-normalized CNR was calculated by dividing the CNR and noise with the square root of the tube current (CNR∕ √ mAs) to exclude the impact of the different tube currents of each protocol. [18][19][20] In addition, to assess the nonlinear contrast resolution, we measured the minimum detectable diameter of contrast rods using the CTP730 low contrast module of the Catphan 604. This module contains nine rods with diameters of 1, 2, 3, 4, 5, 6, 7, 8, and 9 mm, in addition to 15 mm, for each contrast level: 1%, 0.5%, and 0.3%.…”
Section: Cnrmentioning
confidence: 99%
“…Perubahan faktor eksposi tidak memberikan efek yang besar terhadap feature-feature radiomic dari citra CT Scan [21] . [22] . [14] .…”
Section: Ct 𝑁𝑢𝑚𝑏𝑒𝑟unclassified